The Critical Importance of Old World Fruit Bats for Healthy Ecosystems and Economies - Aziz, Sheema Abdul; McConkey, Kim R.; Tanalgo, Krizler; Sritongchuay, Tuanjit; Low, Mary-Ruth; Yong, Joon Yee; Mildenstein, Tammy L.; Nuevo-Diego, Christine Ely; Lim, Voon-Ching; Racey, Paul A. (Frontiers in Ecology and Evolution, 2021)
Despite extensive documentation of the ecological and economic importance of Old World fruit bats (Chiroptera: Pteropodidae) and the many threats they face from humans, negative attitudes towards pteropodids have persisted, fuelled by perceptions of bats as being pests and undesirable neighbours. Such long-term negativity towards bats is now further exacerbated by more recent disease-related concerns, particularly associated with the current COVID-19 pandemic. There remains an urgent need to investigate and highlight the positive and beneficial aspects of bats across the Old World. While previous reviews have summarised these extensively, numerous new studies conducted over the last 36 years have provided further valuable data and insights which warrant an updated review. Here we synthesise research on bat-plant interactions, comprising diet, ecological roles, and ecosystem services, conducted during 1985-2020. We uncovered a total of 311 studies covering 75 out of the known 201 pteropodid species (12.5%), conducted in 47 countries. The majority of studies documented diet (52% of all studies; 67 pteropodid species), followed by foraging movement (49%; 50 pteropodid species), with fewer studies directly investigating the roles played by pteropodids in seed dispersal (24%; 41 pteropodid species), pollination (14%; 19 pteropodid species), and conflict with fruit growers (12%; 11 pteropodid species). Pteropodids were recorded feeding on 1072 plant species from 493 genera and 148 families, with fruits comprising the majority of plant parts consumed, followed by flowers/nectar/pollen, leaves, and other miscellaneous parts. Sixteen pteropodid species have been confirmed to act as pollinators for a total of 21 plant species, and 29 pteropodid species have been confirmed to act as seed dispersers for a total of 311 plant species. Anthropogenic threats disrupting bat-plant interactions in the Old World include hunting, direct persecution, habitat loss/disturbance, invasive species, and climate change, leading to ecosystem-level repercussions. We identify notable research gaps and important research priorities to support conservation action for pteropodids.